Association between level of care and colonization with resistant gram-negative bacteria among nursing-home residents. (22nd June 2021) - Adediran, Timileyin Y; Sethuraman, Kinjal N; Leekha, Surbhi; Roghmann, Mary-Claire
Abstract: In this cross-sectional study, we examined the relationship between resident level of care in the nursing home and colonization with resistant gram-negative bacteria. Residential-care residents were more likely to be colonized with resistant gram-negative bacteria than were postacute care residents (odds ratio, 2.3; 95% confidence interval, 1.40–3.80; P < .001).